FRI0088 Psychological impact in rheumatoid arthritis: role of specific treatment and associated measures. (12th June 2018) - Grapton, X.; ,; Lemesle, P.; Arabian, L.; ,; Strotz, V.; ,
Abstract : Background: Psychological issues in rheumatoid arthritis (RA) are often spontanously mentioned by patients or identified by rheumatologists. Besides classic follow up parameters like DAS28, we have to consider those issues to improve our patients psychological well-being. Objectives: Explore reasons of psychological impact in RA. Analyse in a quantitative way symptoms of discontent and their repercussions. Evaluate consequences of disease treatment on those symptoms and propose recommendations for rheumatologists. Methods: RA cases were collected by a group of 20 private practice rheumatologists in the Paris area. Basic informations about the patient and his disease were provided by his rheumatologist. Questionnaire including 14 items about psychological and life quality involvement was filled in by the patient. Results: 167 cases collected : 82% women, mean age 57 years, 56% moderate and 14% severe disease, 76% ACPA positive, 73% structural damage. Initial DAS28 4, 7. Post treatment DAS28 2.7. Drugs: classic DMARDs 95%, corticosteroids 73%, biological DMARDs 22%, combination therapy 76%. In 82% of the cases, the rheumatologist recommends more than only specific RA drug treatment: rest (47%), physiotherapy, ergotherapy, balneotherapy (42%), adapting professionnel activity and environment, help for housework (33%), psychological support or psychoactive drugs (19%), yoga or other relaxation exercices (11%), balneology… Psychological repercussions are spontaneously mentioned by 71% of the patients. Psychological state is altered by : disease announcement, pain (85%), physical fatigue (71%), handicap (58%), other people's attitude. Are limited : housework (51%), getting about (44%), do-it-yourself (55%), sports (61%), artistic activities (41%), professional activity (29%). Social life is affected by : lack of being listened to (72%), lack of being understood (68%), lack of empathy (49%). RA treatment reduces all those factors by at least one third, except impact on family relations. Before treatment, RA patients report: sleeping trouble (70%), anxiety (57%), lack of motivation (55%), dependency (49%), frustration (42%), lack of self-esteem (37%), concentration problems (35%), disillusion (31%), depression (30%), family tension (29%), isolation (27%) and libido decrease (23%). After treatment, all those factors are 41%–55% less frequent, except libido decrease (−28%). 55% sleep better, 49% aren't depressed anymore, concentration problems diminish by 48% and social life is improved by 50%. Conclusions: There is a major psychological impact in RA patients, with repercussions on their well-being and life quality. This can be improved by specific anti RA treatment, but we must also consider other measures and, if necessary, psychological support and/or psychoactive drugs. All chosen items are improved, except impact on family relations. Disclosure of Interest: None declared